M2‐like macrophage polarization in high lactic acid‐producing head and neck cancer. Issue 6 (19th May 2017) - Ohashi, Toshimitsu; Aoki, Mitsuhiro; Tomita, Hiroyuki; Akazawa, Takashi; Sato, Katsuya; Kuze, Bunya; Mizuta, Keisuke; Hara, Akira; Nagaoka, Hitoshi; Inoue, Norimitsu; Ito, Yatsuji
Abstract : Reprogramming of glucose metabolism in tumor cells is referred to as the Warburg effect and results in increased lactic acid secretion into the tumor microenvironment. We have previously shown that lactic acid has important roles as a pro‐inflammatory and immunosuppressive mediator and promotes tumor progression. In this study, we examined the relationship between the lactic acid concentration and expression of LDHA and GLUT1, which are related to the Warburg effect, in human head and neck squamous cell carcinoma (HNSCC). Tumors expressing lower levels of LDHA and GLUT1 had a higher concentration of lactic acid than those with higher LDHA and GLUT1 expression. Lactic acid also suppressed the expression of LDHA and GLUT1 in vitro . We previously reported that lactic acid enhances expression of an M2 macrophage marker, ARG1, in murine macrophages. Therefore, we investigated the relationship between the lactic acid concentration and polarization of M2 macrophages in HNSCC by measuring the expression of M2 macrophage markers, CSF1R and CD163, normalized using a pan‐macrophage marker, CD68 . Tumors with lower levels of CD68 showed a higher concentration of lactic acid, whereas those with higher levels of CSF1R showed a significantly higher concentration of lactic acid. A similar tendency was observed for CD163 . These results suggest that tumor‐secreted lactic acid is linked to the reduction of macrophages in tumors and promotes induction of M2‐like macrophage polarization in human HNSCC. Abstract : Tumor cells secrete a large amount of lactic acid due to the Warburg effect. This study suggestss that lactic acid negatively regulates the accumulation of macrophages at a tumor site, but promotes M2‐like macrophage polarization in human HNSCC.